Pemodelan Sistem Rancangan Website Toko Ummi Cookies Menggunakan Uml (Unified Modelling Language) - Harlina, Masimbangan Sabarina; Susilowati, Eel; Suharni, Suharni; Herawati, Masimbangan Susana; Atsiilah, Muhammad Fathi (Jurnal Teknologi Dan Sistem Informasi Bisnis, 2025)
Ummi Cookies Shop sells various types of dry cakes (cookies). The shop sells its products by receiving orders from each customer via WhatsApp, the information of which is limited to the community. For new customers who have difficulty obtaining information about the products they want to order. Ummi Cookies shop hopes to be able to promote and sell the cake products offered easily and reach a wider consumer base online with e-commerce media. To realize his hopes, the researcher wants to create a system model for designing a website that is easy for system designers to understand and and meet the needs of users, namely shop owners and shop customers. Website design model Ummi Cookies Shop using UML (Unified Modelling Language). The UML diagrams that will be used are use case diagrams, activity diagrams, and class diagrams.The results of the website design created can be used as a reference by system developers in implementing a website that can help the business activities of Ummi Cookies Shop.